Photoresist composition and patterning method thereof

By introducing free radical photoinitiator into the photoresist, cross-linking and polymerization reaction of metal oxygen clusters and metal oxide nanoparticles is promoted, and the problem of insufficient sensitivity of photoresist in the prior art is solved, and high-precision photolithography is achieved Patterning.

CN119395944APending Publication Date: 2025-02-07张江国家实验室 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411521525.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing metal oxygen clusters and metal oxide nanoparticles are insufficient in the process of high-precision lithography, resulting in blurring and distortion of the lithography pattern, and increasing processing uncertainty and scrap rate.

Method used

A photoresist composition comprising a radical photoinitiator is used, which comprises an organic solvent, a radical photoinitiator, a coinitiator and a metal oxygen cluster and a metal oxide nanoparticle film-forming monomer. Free radical photoinitiators promote unsaturated double bond cross-link polymerization reactions on the surface of metal oxygen clusters and metal oxide nanoparticles by generating free radicals under light conditions, thereby improving the sensitivity of photoresist.

Benefits of technology

It significantly improves the sensitivity and patterning efficiency of photoresist, and can achieve high-precision lithography patterning within the light source range of 250 nanometers to 550 nanometers, meeting the high-precision needs in the field of micro-nano manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119395944A_ABST
    Figure CN119395944A_ABST
Patent Text Reader

Abstract

The invention discloses a photoresist composition and a patterning method thereof, the photoresist composition comprises an organic solvent, a free radical photoinitiator, a co-initiator and a film-forming monomer, the film-forming monomer is metal oxygen cluster and metal oxide nanoparticles, the mass percentage content of the film-forming monomer is 1-30%, the mass percentage content of the co-initiator is 1-30%, and the mass percentage content of the film-forming monomer is 1-30%. The mass percentage content of the free radical photoinitiator is 0.01%-3%, the mass percentage content of the auxiliary initiator is 0-10%, and the mass percentage content of the organic solvent is 57%-98.99%. According to the photoresist composition introduced with the free radical photoinitiator, free radicals are efficiently generated under illumination, cross-linking polymerization of double bonds on the surfaces of metal oxygen clusters and metal oxide nanoparticles is promoted, the photosensitive performance is greatly improved, excellent sensitivity is shown in extreme ultraviolet, electron beams and visible light (within the light source range of 250-600 nanometers), and high-precision photoetching patterning is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, and in particular to a photoresist composition and a patterning method thereof. Background Art

[0002] With the rapid development of micro-nano processing technology, photoresist, as the core material in this field, plays a vital role in promoting the progress of the entire industry. As a key means to achieve photoresist patterning, the diversity of photolithography technology (including g-line, i-line, KrF, ArF, electron beam, extreme ultraviolet and other lithography methods) provides flexible options for different application scenarios. However, the polymer resin monomers widely used in traditional photoresists have inherent defects such as inconsistent molecular weight and molecular formula, poor repeatability, and insufficient etching resistance. These problems limit the accuracy and efficiency of photolithography technology.

[0003] In order to overcome the limitations of polymer resins, researchers have turned their attention to metal oxygen clusters and metal oxide nanoparticles. These materials have shown great potential for use in photoresists due to their unique physical and chemical properties, such as highly uniform molecular structure, excellent etching resistance and good optical properties. Metal oxygen clusters can not only significantly improve the resolution and stability of photoresists, but also optimize the processing technology to a certain extent and reduce production costs.

[0004] Although metal oxo clusters and metal oxide nanoparticles have made significant progress in improving the performance of photoresists, the problem of insufficient sensitivity still needs to be solved. Especially in the field of high-precision processing such as visible light, ultraviolet light, electron beam and extreme ultraviolet lithography, the sensitivity of metal oxo clusters and metal oxide nanoparticles has become a key factor restricting their widespread application. Low sensitivity not only leads to blurring and distortion of lithographic patterns, but also increases uncertainty and scrap rate in the processing process, thus affecting product quality and production efficiency.

[0005] In order to improve the sensitivity of metal oxoclusters and metal oxide nanoparticles, researchers have explored a variety of methods. Among them, adding thiols to achieve thiol-ene click reactions is an effective strategy. By introducing specific functional groups, the interaction between metal oxoclusters and other components of the photoresist is enhanced, thereby improving the overall photosensitivity. However, this method has limited effect in improving the sensitivity of metal oxoclusters and metal oxide nanoparticles patterned under long-wavelength light sources (>365nm), and may also bring about problems such as strong odor, complex reaction conditions, and increased control difficulty. Summary of the invention

[0006] In view of the technical problems existing in the prior art, the photoresist and patterning method thereof provided by the present invention are intended to improve the sensitivity of metal oxygen clusters and metal oxides, and the processing level can reach the micro-nano level.

[0007] In order to achieve the above-mentioned purpose, the present invention provides a photoresist composition, comprising an organic solvent, a free radical photoinitiator, a co-initiator and a film-forming monomer, wherein the film-forming monomer is a metal oxide cluster and a metal oxide nanoparticle, the mass percentage of the film-forming monomer is 1% to 30%, the mass percentage of the free radical photoinitiator is 0.01% to 3%, the mass percentage of the co-initiator is 0 to 10%, and the mass percentage of the organic solvent is 57% to 98.99%.

[0008] Furthermore, the metal oxygen cluster and metal oxide nanoparticles have a particle size of 1 to 3 nm and are formed by combining metal alkoxide and unsaturated organic carboxylic acid.

[0009] Furthermore, the unsaturated organic carboxylic acid is one or more of acrylic acid, methacrylic acid, and 3,3-dimethylacrylic acid.

[0010] Furthermore, the metal in the metal alkoxide is one or more of zinc, nickel, titanium, zirconium, hafnium, cobalt, indium, and tin, and the alcohol ligand is one or more of n-propanol, isopropanol, n-butanol, and isobutanol.

[0011] Furthermore, the free radical photoinitiator has a structure shown in Formula I:

[0012]

[0013] wherein R1 and R2 are each independently selected from a hydrocarbon group having 5 to 10 carbon atoms or a hydrocarbon group having 4 to 16 carbon atoms substituted by a hydrocarbonoxy group, a hydroxyl hydrocarbonoxy group, an ether hydrocarbonoxy group, an alkylenedioxy group, a hydrocarbonamino group, a dialkylamino group, a nitro group or a halogen group, or a coumarin group;

[0014] Preferably, R1 and R2 are each independently selected from coumarinyl, coumarin vinyl, dimethylamino, diethylamino, phenyl, styryl, p-tolyl, p-tolyl vinyl, 3-ethylphenyl, 2-chlorophenyl, 3,4-dimethoxyphenyl, 3,4-dimethoxystyryl, 4-ethoxyphenyl, 3-isobutoxyphenyl, 3,4-methylenedioxyphenyl, 2,3-ethylenedioxyphenyl, 4-(2-hydroxyethoxy)-phenyl, 2-(2-hydroxyethoxy)-phenyl, 4-(4-(6-(amino)-1-propoxy)-phenyl, 4-bromophenyl, 4-nitrophenyl, 3-fluorophenyl, 4-methoxynaphthyl, 4-diethylaminophenyl, 2-dimethylaminophenyl, 3-isopropylaminophenyl, 4-dibutylamino-2-chlorophenyl, furanyl, furanvinyl, N-methylpyrrole, N-methylpyrrolevinyl, 7-(dimethylamino)coumarin, 7-(dimethylamino)coumarinvinyl, 7-(diethylamino)-coumarinyl, 7-(diethylamino)coumarinvinyl.

[0015] More preferably, R1 and R2 are each independently selected from coumarin, coumarin vinyl, 7-(dimethylamino)coumarin, 7-(dimethylamino)coumarin vinyl, 7-(diethylamino)coumarin, 7-(diethylamino)coumarin vinyl, furanyl, furan vinyl, N-methylpyrrole, N-methylpyrrole vinyl, 3,4-dimethoxyphenyl, 3,4-dimethoxystyryl, phenyl, styryl, p-tolyl, p-tolyl vinyl.

[0016] Furthermore, the co-initiator is one or more of diphenyliodonium hexafluorophosphate, triethanolamine, N-methyldiethanolamine, ethyl 4-dimethylaminobenzoate, N-phenylglycine, and N,N-dimethyl-p-toluidine.

[0017] Furthermore, the organic solvent includes one or more of toluene, o-xylene, m-xylene, p-xylene, m-trimethylbenzene, propylene glycol methyl ether acetate, propylene glycol methyl ether, chloroform, acetone, cyclopentanone, cyclohexanone, 4-methyl-2-pentanone, 2-heptanone, methanol, ethanol, n-propanol, isopropanol, butyl acetate and ethyl lactate.

[0018] The present invention also provides a method for patterning a photoresist composition, comprising the following steps: applying the photoresist composition on a substrate and drying it to form a photoresist film, and performing photolithographic exposure on the photoresist film and then placing it in a developer for development to form a photolithographic pattern.

[0019] Furthermore, the photolithography exposure method is visible light lithography, electron beam lithography or extreme ultraviolet lithography.

[0020] Furthermore, the light source of the visible light lithography method is visible light with a wavelength of 365 to 600 nm and a dose of 10 to 500 mJ·cm -2 The electron beam lithography method is to expose the electron beam using an electron beam exposure machine, with a dose of 50 to 50000 pC cm -1 The light source of the EUV lithography method is EUV light with a wavelength of 13.5 nm and a dose of 5 to 500 mJ·cm -2 .

[0021] In summary, the present invention has the following beneficial effects:

[0022] 1. In the photoresist composition of the present invention, the introduction of a free radical photoinitiator achieves a significant improvement in photosensitivity. Under light conditions, the photoinitiator can efficiently generate a large number of free radicals, which then quickly act on the unsaturated double bonds on the surface of metal oxygen clusters and metal oxide nanoparticles, prompting them to undergo cross-linking polymerization reactions. This mechanism not only significantly enhances the overall sensitivity of the material, but also cleverly achieves an improvement in photosensitivity without significantly changing the original properties of the metal oxygen clusters and metal oxides.

[0023] Second, the photoinitiator of the present invention can significantly improve the imaging quality and resolution of patterns in UV / visible light lithography, electron beam lithography or extreme ultraviolet lithography. The prepared photoresist exhibits excellent sensitivity in the light source range of 250 nanometers to 550 nanometers, enabling the photoresist to accurately realize photolithographic patterning in this wavelength range, providing a high-performance material foundation for the field of micro-nano manufacturing.

[0024] 3. After the photoresist is exposed, the solubility of the exposed area and the non-exposed area in the developer shows a significant difference. This feature ensures that the photolithography pattern can be accurately formed after the development process, and shows high efficiency in the photolithography process. The feature size of the processed pattern can reach the micro-nano level, meeting the stringent requirements of modern semiconductor and micro-nano manufacturing fields for high-precision patterning. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 Schematic diagram of the mechanism of BDO1 generating free radicals through hydrogen transfer in the present invention.

[0027] Figure 2 This is the Jablonski simplified diagram of BDO1 in the present invention.

[0028] Figure 3 This is the frontier molecular orbital diagram of BDO1 calculated by DFT and TDDFT in the present invention.

[0029] Figure 4 : This is the ESR spectrum of BDO1 under 450nm LED irradiation in N2 and air atmospheres in the present invention.

[0030] Figure 5 Schematic diagram of molecular orbital interaction in the triplet hydrogen transfer process of the present invention.

[0031] Figure 6 Schematic diagram of the cross-linking mechanism of the outer layer ligands of the film-forming monomers induced by BDO1-H-FR in the present invention.

[0032] Figure 7 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 1 of the present invention.

[0033] Figure 8 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 2 of the present invention.

[0034] Fig. 9 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 3 of the present invention.

[0035] Fig.10 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 4 of the present invention.

[0036] Fig.11 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 5 of the present invention.

[0037] Fig.12 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 6 of the present invention.

[0038] Fig.13 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 7 of the present invention.

[0039] Fig.14 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 8 of the present invention.

[0040] Fig.15 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 9 of the present invention.

[0041] Fig.16 This is the X-ray powder diffraction pattern of the film-forming monomer in Example 10 of the present invention.

[0042] Fig.17 This is a picture taken with a research upright microscope after the photoresist composition in Example 1 of the present invention is patterned.

[0043] Fig.18 This is a picture taken with a research upright microscope after the photoresist composition in Example 2 of the present invention is patterned.

[0044] Fig.19 This is a picture taken with a research upright microscope after the photoresist composition in Example 3 of the present invention is patterned.

[0045] Fig. 20 This is a picture taken with a research upright microscope after the photoresist composition in Example 4 of the present invention is patterned.

[0046] Fig.21 This is a picture taken with a research upright microscope after the photoresist composition in Example 5 of the present invention is patterned.

[0047] Fig. 22 The picture was taken with a research upright microscope after the photoresist composition in Example 6 of the present invention was patterned.

[0048] Fig.23This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 7 of the present invention is patterned.

[0049] Fig.24 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 8 of the present invention is patterned.

[0050] Fig.25 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 9 of the present invention is patterned.

[0051] Fig.26 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Example 10 of the present invention is patterned.

[0052] Fig. 27 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 1 of the present invention was patterned.

[0053] Fig.28 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 2 of the present invention was patterned.

[0054] Fig.29 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 3 of the present invention was patterned.

[0055] Fig.30 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 4 of the present invention was patterned.

[0056] Fig.31 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 5 of the present invention was patterned.

[0057] Fig.32 The picture was taken with a research upright microscope after the photoresist composition in Comparative Example 6 of the present invention was patterned.

[0058] Fig.33 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Comparative Example 7 of the present invention was patterned.

[0059] Fig.34 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Comparative Example 8 of the present invention was patterned.

[0060] Fig.35 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Comparative Example 9 of the present invention is patterned.

[0061] Fig.36 This is a picture taken by a high-resolution scanning electron microscope after the photoresist composition in Comparative Example 10 of the present invention is patterned. DETAILED DESCRIPTION

[0062] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0063] Unless otherwise specified, the terms used herein have the following meanings: The term "halogen" used in the present invention includes fluorine, chlorine, bromine and iodine; "hydrocarbon" includes straight-chain hydrocarbon groups and branched hydrocarbon groups.

[0064] The invention provides a photoresist composition, comprising an organic solvent, a free radical photoinitiator, an auxiliary initiator and a film-forming monomer, wherein the film-forming monomer is a metal oxygen cluster and a metal oxide nanoparticle, the mass percentage of the film-forming monomer is 1% to 30%, the mass percentage of the free radical photoinitiator is 0.01% to 3%, the mass percentage of the auxiliary initiator is 0 to 10%, and the mass percentage of the organic solvent is 57% to 98.99%.

[0065] The free radical photoinitiator in the photoresist composition of the present invention, i.e., its interaction with the co-initiator, can increase the sensitivity of all metal oxygen clusters and metal oxide nanoparticle film-forming monomers with unsaturated double bonds. At the same time, the free radical photoinitiator used in the present invention can realize patterning under a long wavelength light source (>365nm).

[0066] Furthermore, the metal oxygen cluster and metal oxide nanoparticles have a particle size of 1 to 3 nm and are formed by combining metal alkoxide and unsaturated organic carboxylic acid.

[0067] Furthermore, the unsaturated organic carboxylic acid is one or more of acrylic acid, methacrylic acid, and 3,3-dimethylacrylic acid.

[0068] Furthermore, the metal in the metal alkoxide is one or more of zinc, nickel, titanium, zirconium, hafnium, cobalt, indium, and tin, and the alcohol ligand is one or more of n-propanol, isopropanol, n-butanol, and isobutanol.

[0069] The metal oxygen cluster and metal oxide nanoparticle film-forming monomers of the present scheme are prepared at room temperature and can be obtained by filtering and post-processing. The process is simple, and the unsaturated bonds in the outer layer can react with free radical photoinitiators under visible light to form cross-linked polymers.

[0070] Furthermore, the free radical photoinitiator has a structure shown in Formula I:

[0071]

[0072] wherein R1 and R2 are each independently selected from a hydrocarbon group having 5 to 10 carbon atoms or a hydrocarbon group having 4 to 16 carbon atoms substituted by a hydrocarbonoxy group, a hydroxyl hydrocarbonoxy group, an ether hydrocarbonoxy group, an alkylenedioxy group, a hydrocarbonamino group, a dialkylamino group, a nitro group or a halogen group, or a coumarin group;

[0073] Preferably, R1 and R2 are each independently selected from coumarinyl, coumarin vinyl, dimethylamino, diethylamino, phenyl, styryl, p-tolyl, p-tolyl vinyl, 3-ethylphenyl, 2-chlorophenyl, 3,4-dimethoxyphenyl, 3,4-dimethoxystyryl, 4-ethoxyphenyl, 3-isobutoxyphenyl, 3,4-methylenedioxyphenyl, 2,3-ethylenedioxyphenyl, 4-(2-hydroxyethoxy)-phenyl, 2-(2-hydroxyethoxy)-phenyl, 4-(4-(6-(amino)-1-propoxy)-phenyl, 4-bromophenyl, 4-nitrophenyl, 3-fluorophenyl, 4-methoxynaphthyl, 4-diethylaminophenyl, 2-dimethylaminophenyl, 3-isopropylaminophenyl, 4-dibutylamino-2-chlorophenyl, furanyl, furanvinyl, N-methylpyrrole, N-methylpyrrolevinyl, 7-(dimethylamino)coumarin, 7-(dimethylamino)coumarinvinyl, 7-(diethylamino)-coumarinyl, 7-(diethylamino)coumarinvinyl;

[0074] More preferably, R1 and R2 are each independently selected from coumarin, coumarin vinyl, 7-(dimethylamino)coumarin, 7-(dimethylamino)coumarin vinyl, 7-(diethylamino)coumarin, 7-(diethylamino)coumarin vinyl, furanyl, furan vinyl, N-methylpyrrole, N-methylpyrrole vinyl, 3,4-dimethoxyphenyl, 3,4-dimethoxystyryl, phenyl, styryl, p-tolyl, p-tolyl vinyl.

[0075] The partial structural formula is as follows:

[0076]

[0077] The free radical photoinitiator disclosed in this scheme has a unique electronic configuration, that is, after absorbing ultraviolet light to reach the lowest excited state, the highest occupied orbital (n orbital of carbonyl) and the lowest empty orbital (π* orbital of carbonyl) in the ground state are both half-filled, which greatly promotes the occurrence of intramolecular or intermolecular hydrogen abstraction reactions (i.e., Norrish II type reactions). This highly efficient reaction activity enables the free radical photoinitiator to respond quickly to ultraviolet light irradiation in the photoresist, thereby effectively initiating polymerization reactions, improving the sensitivity and reaction rate of the photoresist, and ensuring the accuracy and efficiency of the photolithography process.

[0078] Furthermore, the co-initiator is one or more of diphenyliodonium hexafluorophosphate, triethanolamine, N-methyldiethanolamine, ethyl 4-dimethylaminobenzoate, N-phenylglycine, and N,N-dimethyl-p-toluidine.

[0079] Furthermore, the organic solvent includes one or more of toluene, o-xylene, m-xylene, p-xylene, m-trimethylbenzene, propylene glycol methyl ether acetate, propylene glycol methyl ether, chloroform, acetone, cyclopentanone, cyclohexanone, 4-methyl-2-pentanone, 2-heptanone, methanol, ethanol, n-propanol, isopropanol, butyl acetate and ethyl lactate.

[0080] The preferred solvents with high solubility in this scheme ensure that the material can be fully dissolved and form a uniform film, ensure the high precision and high quality of the photolithography patterning, and prevent the film inhomogeneity caused by the crystallization phenomenon. The selection of these solvents ensures the uniform coating of the photoresist. In order to further verify the advantages of these solvents in forming photoresist films, we used atomic force microscopy to accurately measure the roughness of the film. The results show that the roughness of the photoresist films prepared by these solvents is less than 0.8 nanometers, which is much lower than the requirements of the photolithography process for the film roughness, which fully proves the excellent performance of these solvents in forming high-quality, high-uniformity films.

[0081] In addition, the surface morphology of the films was carefully observed using a research upright microscope. The results showed that the surfaces of these films were smooth and free of defects, further verifying the applicability of these solvents in photoresist preparation.

[0082] The present invention also provides a method for patterning a photoresist composition, comprising the following steps: applying the photoresist composition on a substrate, and forming a photoresist film by baking or drying at room temperature, and then exposing the photoresist film to photolithography and placing it in a developer to develop and form a photolithography pattern.

[0083] Furthermore, the developer includes one or more of toluene, o-xylene, m-xylene, p-xylene, m-trimethylbenzene, propylene glycol methyl ether acetate, propylene glycol methyl ether, chloroform, acetone, cyclopentanone, cyclohexanone, 4-methyl-2-pentanone, 2-heptanone, methanol, ethanol, n-propanol, isopropanol, butyl acetate and ethyl lactate.

[0084] In some embodiments, the photoresist composition may be coated on the substrate using methods and devices commonly used in the art, such as a coating machine. The rotation speed of the coating machine is controlled to be 400 to 6000 rpm, and the acceleration is 500 to 12000 rpm s -1 The photoresist composition is coated on a substrate. Examples of the substrate include, but are not limited to, a glass substrate, a quartz substrate, a silicon wafer substrate, a polymer material substrate, and the like.

[0085] In some embodiments, before placing the photoresist composition on the substrate, the step of filtering the photoresist using a filter membrane is further included. The pore size of the filter membrane can be a conventional small pore size, preferably 0.22 μm.

[0086] In some embodiments, the drying to form the photoresist film can be performed using conventional methods and devices, such as a curing machine, wherein the temperature of the curing machine is controlled to be 35-60° C. to dry the photoresist composition to form a film.

[0087] In some embodiments, the method of photolithography exposure is visible light lithography, ultraviolet lithography, electron beam lithography, and extreme ultraviolet lithography. The light source of the visible light lithography is visible light with a wavelength of 365 to 600 nm and a dose of 10 to 500 mJ·cm -2 The light source of the ultraviolet lithography method has a wavelength of 193 to 365 nm and a dose of 5 to 500 mJ·cm -2 The electron beam lithography method is to use an electron beam exposure machine to expose the surface with a dose of 50 to 50000 pC·cm -1 The light source of the EUV lithography method is EUV light with a wavelength of 13.5 nm and a dose of 5 to 500 mJ·cm -2 .

[0088] Example 1

[0089] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g of titanium n-propoxide and 12mL of methacrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15 minutes. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12 hours. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0090] Free radical photoinitiators are selected as follows:

[0091]

[0092] Take 0.02g of free radical photoinitiator (1,3-di(furan-2-yl)prop-2-en-1-one), 0.1g of metal oxygen cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of chloroform, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0093] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a coating machine at a rotation speed of 400 rpm and an acceleration of 500 rpm s -1The substrate was then placed under a xenon lamp with a wavelength of 254 nm. When the dose reached 10 mJ·cm -2 , stop exposure. Place the substrate in cyclohexanone for 15 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a research upright microscope to photograph the pattern obtained after exposure.

[0094] Example 2

[0095] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g of zirconium n-propoxide and 12mL of methacrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15 minutes. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12 hours. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0096] The free radical photoinitiator is selected as follows

[0097]

[0098] Take 0.02g of free radical photoinitiator (1,3-bis(1-methyl-1H-pyrrol-2-yl)prop-2-en-1-one), 0.2g of metal oxygen cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of butyl acetate, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0099] The prepared photoresist solution was dropped onto the surface of a clean quartz substrate and placed in a coating machine at a rotation speed of 4000 rpm and an acceleration of 8000 rpm s -1 The substrate was then placed under a xenon lamp with a wavelength of 254 nm. When the dose reached 300 mJ·cm -2 , stop exposure. Place the substrate in methyl isobutyl ketone for 20 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a research upright microscope to photograph the pattern obtained after exposure.

[0100] Example 3

[0101] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: 1g of hafnium n-propoxide and 12mL of methacrylic acid are added to a 20mL sample bottle and stirred at room temperature for 15min. Then, the sample bottle cap is tightly closed and sealed with a sealing film. After standing for 2 to 3 weeks, a solid appears, the liquid is poured out, the solid is washed with n-hexane, and dried at 45°C in a vacuum environment for 12h. A white solid is obtained, i.e., a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0102] Free radical photoinitiators are selected as follows:

[0103]

[0104] Take 0.02g of free radical photoinitiator (1,3-bis(benzo[d][1,3]dioxol-5-yl)prop-2-en-1-one), 0.25g of metal oxygen cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of propylene glycol methyl ether acetate, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0105] The prepared photoresist solution was dropped onto the surface of a clean silicon wafer substrate and placed in a coating machine at a rotation speed of 6000 rpm and an acceleration of 12000 rpm s -1 The substrate was then placed under a xenon lamp with a wavelength of 254 nm. When the dose reached 500 mJ·cm -2 , stop exposure. Place the substrate in cyclopentanone for 15 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a research upright microscope to photograph the pattern obtained after exposure.

[0106] Example 4

[0107] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g of titanium n-propoxide, 1g of zirconium n-propoxide and 12mL of methacrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15 minutes. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12 hours. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0108] Free radical photoinitiators are selected as follows:

[0109]

[0110] Take 0.02g of free radical photoinitiator (1,5-di(furan-2-yl)penta-1,4-dien-3-one), 0.1g of metal oxygen cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of chloroform, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0111] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a coating machine at a rotation speed of 400 rpm and an acceleration of 500 rpm s -1 The substrate was then placed under a xenon lamp with a wavelength of 500 nm. When the dose reached 10 mJ·cm -2 , stop exposure. Place the substrate in cyclohexanone for 15 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a research upright microscope to photograph the pattern obtained after exposure.

[0112] Example 5

[0113] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g of titanium n-propoxide, 1g of hafnium n-propoxide and 12mL of methacrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15min. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12h. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0114] Free radical photoinitiators are selected as follows:

[0115]

[0116] Take 0.02g of free radical photoinitiator (1,5-bis(1-methyl-1H-pyrrol-2-yl)penta-1,4-dien-3-one), 0.2g of metal oxide cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of butyl acetate, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0117] The prepared photoresist solution was dropped onto the surface of a clean quartz substrate and placed in a coating machine at a rotation speed of 4000 rpm and an acceleration of 8000 rpm s -1 The substrate was then placed under a xenon lamp with a wavelength of 500 nm. When the dose reached 300 mJ·cm -2, stop exposure. Place the substrate in methyl isobutyl ketone for 20 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a research upright microscope to photograph the pattern obtained after exposure.

[0118] Example 6

[0119] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g zirconium n-propoxide, 1g hafnium n-propoxide and 12mL methacrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15min. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12h. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0120] Free radical photoinitiators are selected as follows:

[0121]

[0122] Take 0.02g of free radical photoinitiator (1,5-bis(benzo[d][1,3]dioxol-5-yl)penta-1,4-dien-3-one), 0.25g of metal oxide clusters and metal oxide nanoparticle film-forming monomers and dissolve them in 2g of propylene glycol methyl ether acetate, stir or ultrasonicate to completely dissolve them. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0123] The prepared photoresist solution was dropped onto the surface of a clean silicon wafer substrate and placed in a coating machine at a rotation speed of 6000 rpm and an acceleration of 12000 rpm s -1 The substrate was then placed under a xenon lamp with a wavelength of 500 nm. When the dose reached 500 mJ·cm -2 , stop exposure. Place the substrate in cyclopentanone for 15 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a research upright microscope to photograph the pattern obtained after exposure.

[0124] Example 7

[0125] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g of titanium n-propoxide, 1g of zirconium n-propoxide, 1g of hafnium n-propoxide and 12mL of methacrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15 minutes. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12 hours. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0126] Free radical photoinitiators are selected as follows:

[0127]

[0128] Take 0.02g of free radical photoinitiator (7-(dimethylamino)-3-(3-phenylacryloyl)-2H-chromen-2-one), 0.04g of N-methyldiethanolamine, 0.3g of metal oxide clusters and metal oxide nanoparticle film-forming monomers and dissolve them in 2g of propylene glycol methyl ether acetate, stir or ultrasonicate to completely dissolve them. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0129] The prepared photoresist solution was dropped onto the surface of a clean silicon wafer substrate and placed in a coating machine at a rotation speed of 6000 rpm and an acceleration of 12000 rpm s -1 The substrate was exposed to light with an electron beam lithography machine. When the dose reached 50 pC·cm -1 , stop exposure. Place the substrate in cyclopentanone for 60 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a high-resolution scanning electron microscope to photograph the pattern obtained after exposure.

[0130] Example 8

[0131] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g of titanium n-butoxide and 12mL of acrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15min. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12h. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0132] Free radical photoinitiators are selected as follows:

[0133]

[0134] Take 0.02g of free radical photoinitiator (7-(dimethylamino)-3-(3-(furan-2-yl)acryloyl)-2H-chromen-2-one), 0.08g of N-methyldiethanolamine, 0.3g of metal oxide cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of propylene glycol methyl ether acetate, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0135] The prepared photoresist solution was dropped onto the surface of a clean silicon wafer substrate and placed in a coating machine at a rotation speed of 6000 rpm and an acceleration of 12000 rpm s -1 The substrate was exposed to light with an electron beam exposure machine. When the dose reached 50000 pC·cm -1 , stop exposure. Place the substrate in cyclohexanone for 60 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a high-resolution scanning electron microscope to photograph the pattern obtained after exposure.

[0136] Example 9

[0137] The preparation method of the metal oxygen cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: Take 1g of zirconium n-butoxide and 12mL of 3,3-dimethylacrylic acid and add them to a 20mL sample bottle, and stir at room temperature for 15 minutes. Then, cover the sample bottle cap tightly and seal it with a sealing film. After standing for 2 to 3 weeks, a solid appears, pour out the liquid, wash the solid with n-hexane, and dry it at 45°C in a vacuum environment for 12 hours. A white solid is obtained, which is a metal oxygen cluster and metal oxide nanoparticle film-forming monomer.

[0138] Free radical photoinitiators are selected as follows:

[0139]

[0140] Take 0.02g of free radical photoinitiator (7-(diethylamino)-3-(3-(1-methyl-1H-pyrrol-2-yl)acryloyl)-2H-chromen-2-one), 0.08g of triethanolamine, 0.3g of metal oxide cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of propylene glycol methyl ether acetate, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0141] The prepared photoresist solution was dropped onto the surface of a clean silicon wafer substrate and placed in a coating machine at a rotation speed of 6000 rpm and an acceleration of 12000 rpm s -1 The substrate was then exposed to extreme ultraviolet light for 30 seconds. -2 , stop exposure. Place the substrate in cyclopentanone for 60 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a high-resolution scanning electron microscope to photograph the pattern obtained after exposure.

[0142] Example 10

[0143] The preparation method of the metal oxide cluster and metal oxide nanoparticle film-forming monomer in this embodiment is as follows: 1g of hafnium n-butoxide and 12mL of methacrylic acid are added to a 20mL sample bottle and stirred at room temperature for 15min. Then, the sample bottle cap is tightly closed and sealed with a sealing film. After standing for 2 to 3 weeks, a solid appears, the liquid is poured out, the solid is washed with n-hexane, and dried at 45°C in a vacuum environment for 12h. A white solid is obtained, i.e., a metal oxide cluster and metal oxide nanoparticle film-forming monomer.

[0144] Free radical photoinitiators are selected as follows:

[0145]

[0146] Take 0.02g of free radical photoinitiator (3-(3-(benzo[d][1,3]dioxol-5-yl)acryloyl)-7-(diethylamino)-2H-chromen-2-one), 0.08g of triethanolamine, 0.3g of metal oxygen cluster and metal oxide nanoparticle film-forming monomer and dissolve them in 2g of propylene glycol methyl ether acetate, stir or ultrasonicate to make them completely dissolved. Then filter the photoresist solution twice using a filter membrane with a pore size of 0.22μm.

[0147] The prepared photoresist solution was dropped onto the surface of a clean silicon wafer substrate and placed in a coating machine at a rotation speed of 6000 rpm and an acceleration of 12000 rpm s -1 The substrate was then exposed to extreme ultraviolet light for 30 seconds. -2 , stop exposure. Place the substrate in cyclohexanone for 60 seconds, and use a nitrogen air gun to blow dry the residual developer on the surface of the substrate material. Finally, use a high-resolution scanning electron microscope to photograph the pattern obtained after exposure.

[0148] Comparative Example 1

[0149] The difference between this embodiment and embodiment 1 is that no free radical photoinitiator and co-initiator are added.

[0150] Comparative Example 2

[0151] The difference between this embodiment and embodiment 2 is that no free radical photoinitiator and co-initiator are added.

[0152] Comparative Example 3

[0153] The difference between this embodiment and embodiment 3 is that no free radical photoinitiator and co-initiator are added.

[0154] Comparative Example 4

[0155] The difference between this embodiment and embodiment 4 is that no free radical photoinitiator and co-initiator are added.

[0156] Comparative Example 5

[0157] The difference between this embodiment and embodiment 5 is that no free radical photoinitiator and co-initiator are added.

[0158] Comparative Example 6

[0159] The difference between this embodiment and embodiment 6 is that no free radical photoinitiator and co-initiator are added.

[0160] Comparative Example 7

[0161] The difference between this embodiment and embodiment 7 is that no free radical photoinitiator and co-initiator are added.

[0162] Comparative Example 8

[0163] The difference between this embodiment and embodiment 8 is that no free radical photoinitiator and co-initiator are added.

[0164] Comparative Example 9

[0165] The difference between this embodiment and embodiment 9 is that no free radical photoinitiator and co-initiator are added.

[0166] Comparative Example 10

[0167] The difference between this embodiment and embodiment 10 is that no free radical photoinitiator and co-initiator are added. The test conditions of each embodiment and comparative example are shown in Table 1:

[0168] Table 1 List of experimental conditions for each embodiment and comparative example

[0169]

[0170]

[0171] Tests, results and analysis

[0172] (1) Research results on the mechanism of combined action of free radical photoinitiators and co-initiators

[0173] BDO1 free radical photoinitiator: (1E,4E)-1,5-bis(benzo[d][1,3]dioxol-5-yl)penta-1,4-dien-3-one

[0174]

[0175] BDO1 contains a ketone structure, and the proton on the methylene group on the piperonyl ring is donated to the carbonyl group to undergo a hydrogen abstraction reaction. According to the mechanism of the photochemical reaction of carbonyl compounds, the σ(CH) bond in the half-filled highest occupied molecular orbital (HOMO) will attack the C=O group in the half-filled lowest unoccupied molecular orbital (LUMO). Past studies have shown that the methylene group in the piperonyl ring can act as a hydrogen donor. Therefore, Figure 1 The most reasonable mechanism of the photoinitiated process was proposed.

[0176] The experiment used electron spin resonance (ESR) and theoretical calculation to prove the feasibility of the reaction mechanism of BDO1 to generate free radicals. The ESR experiment was carried out on BDO1 under 450nm light, and the obtained ESR spectrum is shown in the figure below. Figure 4 The hyperfine coupling constant of the adduct formed by the free radical generated by BDO1 and PBN is H =2.2,ɑ N =14.2, corresponding to the BDO1-H-FR free radical.

[0177] Subsequently, the experiment carried out theoretical calculations and first obtained the simplified Jablonski diagram of BDO1 ( Figure 2 ). BDO1 is excited from the ground state (S0) to the singlet state (S1), and then relaxes to the *S1 state via vibrational relaxation (Vr). Figure 3 is the frontier molecular orbital of BDO1 in different states. The energy gap between the *S1 state and the T3 state is small, and the spin-orbit coupling (SOC) is large, which is conducive to the *S1 state entering the triplet state (T3, T2 and T1) through intersystem crossing (ISC). Then, by calculating Figure 1 The difference between the total energy of the products and the total energy of the reactants listed in the table gives the reaction energy of BDO1 in different states (Table 2). In the ground state, the reaction energy of BDO1 is positive, indicating that the reaction is impossible. In contrast, in the S1, T3, T2, and T1 states, the ΔE values ​​are all negative, indicating that the reaction is reasonable. The low absolute fluorescence yield and the capture of different free radicals under air and nitrogen conditions ( Figure 4 ), indicating that BDO1 in the S1 state is more inclined to ISC rather than generate free radicals. Therefore, the photochemical reaction is likely to occur in the triplet state. According to the frontier molecular orbital theory, for organic photochemical reactions, the lower the frontier molecular orbital energy gap of the reactant molecule, the higher the orbital positive overlap, and the easier it is to react. The frontier molecular orbital theory and the principle of maximum orbital overlap are used to explain the generation process of free radicals ( Figure 5). In the T3 state, the FMO interaction between the σ(CH) bond and the p orbital of the C=O group is hindered, and the energy gap between HOMO-2 and LUMO is large, which is not conducive to the generation of free radicals. In the T1 state, the half-filled HOMO and LUMO and the smallest energy gap, the π-π*FMO interaction between the σ(CH) bond and the carbonyl π orbital make the maximum orbital overlap. Theoretical calculations show that BDO1 generates corresponding free radicals in the T1 state process.

[0178] Table 2 Reaction energy of substances

[0179] PI BDO1 E(M)-GS / Ha -1107.29651 <![CDATA[E(M)-S1 / Ha]]> -1107.19409 <![CDATA[E(M)-T3 / Ha]]> -1107.19779 <![CDATA[ΔE(S1T3) / eV]]> 0.45 E(M-OH) / Ha -1107.88152 E(MH) / Ha -1106.64285 ΔE / Kcal / molvsGS 43.12 <![CDATA[ΔE / Kcal / molvsS1]]> -91.13 <![CDATA[ΔE / Kcal / molvsT3]]> -80.20 <![CDATA[ΔE / Kcal / molvsT2]]> -36.40 <![CDATA[ΔE / Kcal / molvsT1]]> -36.40

[0180] In summary, the proton on the methylene group of the piperonyl ring is donated to the keto structure of BDO1 to generate BDO1-H-FR radical and BDO1-OH-FR radical ( Figure 1 ), the BDO1-OH-FR radical has a large steric hindrance and is not captured by PBN. It also shows that the BDO1-OH-FR radical cannot initiate monomer polymerization, so the free radical that initiates monomer polymerization is the BDO1-H-FR radical.

[0181] BDO1-H-FR free radical plays a crucial role in the photoresist patterning process. As an active center, it can initiate cross-linking reactions of double bonds in the outer layer ligands of metal oxygen clusters and metal oxide nanoparticle film-forming monomers ( Figure 6 ). This chemical reaction not only enhances the structural stability of the photoresist composition, but also ensures the accuracy and clarity of the pattern in the subsequent photoresist development process under the condition of reduced developer solubility through the formation of chemical bonds.

[0182] (2) Analysis of patterning results of photoresist compositions prepared in various examples and comparative examples

[0183] The patterning results of the photoresist compositions prepared in the examples and comparative examples are shown in Table 3:

[0184] Table 3 Patterning results of photoresist compositions prepared in Examples and Comparative Examples

[0185] sample With or without pattern Is the pattern collapsed? Is the top of the pattern lost? Pattern quality Example 1 yes no no good Example 2 yes no no good Example 3 yes no no good Example 4 yes no no good Example 5 yes no no good Example 6 yes no no good Example 7 yes no no good Example 8 yes no no good Example 9 yes no no good Example 10 yes no no good Comparative Example 1 no yes yes Difference Comparative Example 2 no yes yes Difference Comparative Example 3 no yes yes Difference Comparative Example 4 no yes yes Difference Comparative Example 5 no yes yes Difference Comparative Example 6 no yes yes Difference Comparative Example 7 A little bit yes yes Difference Comparative Example 8 A little bit yes yes Difference Comparative Example 9 no yes yes Difference Comparative Example 10 no yes yes Difference

[0186] The free radical photoinitiator containing carbonyl group disclosed in the present invention shows excellent performance in photoresist composition. The photoinitiator shows extremely high sensitivity to electron beam and light of various spectral ranges (including ultraviolet / visible light and extreme ultraviolet light). After absorbing these radiation energies, the photoinitiator can rapidly undergo hydrogen abstraction reaction to produce free radicals with extremely high activity. These free radicals then trigger polymerization reaction of unsaturated bonds on the surface of metal oxygen clusters and metal oxide nanoparticles, resulting in significant changes in the solubility of oxygen clusters or nanoparticles. This characteristic is crucial in the subsequent development process because it can accurately control the formation and resolution of patterns.

[0187] In order to verify the actual effect of this photoinitiator in the photoresist composition, we designed and implemented a series of control experiments. Figures 7 to 16 The successfully prepared metal oxide clusters and metal oxide nanoparticle film-forming monomers are shown, which indicates that the reason for the failure of successful patterning in the comparative examples and embodiments is not due to the problem of the film-forming monomers.

[0188] Under the irradiation of UV / visible light source, we observed that the experimental group samples (Examples 1 to 6) with the addition of the photoinitiator successfully formed clear and uniform patterns on the photoresist layer (such as Figures 17 to 22 These patterns have sharp edges and uniform line widths, fully demonstrating the excellent performance of photoinitiators in UV / visible light lithography. In contrast, the control samples (Comparative Examples 1 to 6) without the addition of photoinitiators failed to form any visible patterns after development (as shown in Figure 2). Figures 27 to 32 This further demonstrates the key role of photoinitiators in the pattern formation process.

[0189] In addition, we also used an electron beam exposure machine to perform exposure experiments on the photoresist composition. Under low-dose radiation conditions, the experimental group samples (Example 7) with the addition of free radical photoinitiator and co-initiator successfully formed high-quality patterns (such as Fig.23 These patterns have clear lines, sharp edges, and good integrity. However, the control sample (Comparative Example 7) without the addition of free radical photoinitiator and co-initiator has its pattern completely washed away after development (as shown in Figure 7). Fig.33 This once again proves the necessity of photoinitiators in electron beam lithography. Under high-dose radiation conditions, the experimental group samples (Example 8) with added photoinitiators and co-initiators also obtained high-quality patterns (as shown in Fig.24 ), while the control group samples without addition showed pattern collapse and distortion (as shown in Fig.34 shown).

[0190] In order to further verify the performance of the photoinitiator, the examples and comparative examples also used an extreme ultraviolet exposure machine to conduct exposure experiments. Under low-dose radiation conditions, the experimental group sample (Example 9) with the addition of free radical photoinitiator and co-initiator successfully formed a clear line pattern (such as Fig.25 However, the control sample without adding photoinitiator and co-initiator failed to form any visible lines (as shown in Fig.35 Under high-dose radiation conditions, the experimental group sample (Example 10) with the addition of photoinitiator and co-initiator obtained a high-quality pattern (as shown in Fig.26 ), while the control group samples without addition showed pattern collapse and distortion (as shown in Fig.36 shown).

[0191] In summary, the free radical photoinitiator containing a carbonyl group disclosed in the present invention exhibits excellent performance in a photoresist composition. Whether in ultraviolet / visible light lithography, electron beam lithography or extreme ultraviolet lithography, the photoinitiator can significantly improve the sensitivity of metal oxygen clusters and metal oxide nanoparticle film-forming monomers and improve patterning efficiency. At the same time, the imaging quality and resolution of the pattern can also be improved. At the same time, the photoinitiator can also ensure the stability and integrity of the pattern during the development process, thereby meeting the demand for high-precision patterning in modern micro-nano manufacturing and semiconductor production.

[0192] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A photoresist composition, characterized in that The photoresist composition comprises an organic solvent, a free radical photoinitiator, a co-initiator and a film-forming monomer, wherein the film-forming monomer is a metal oxide cluster and a metal oxide nanoparticle, the mass percentage of the film-forming monomer is 1% to 30%, the mass percentage of the free radical photoinitiator is 0.01% to 3%, the mass percentage of the co-initiator is 0 to 10%, and the mass percentage of the organic solvent is 57% to 98.99%.

2. The photoresist composition according to claim 1, characterized in that The metal oxygen cluster and metal oxide nanoparticles have a particle size of 1 to 3 nm and are formed by combining metal alkoxide and unsaturated organic carboxylic acid.

3. The photoresist composition according to claim 2, characterized in that The unsaturated organic carboxylic acid is one or more of acrylic acid, methacrylic acid and 3,3-dimethylacrylic acid.

4. The photoresist composition according to claim 2, characterized in that The metal in the metal alkoxide is one or more of zinc, nickel, titanium, zirconium, hafnium, cobalt, indium and tin, and the alcohol ligand is one or more of n-propanol, isopropanol, n-butanol and isobutanol.

5. The photoresist composition according to claim 1, characterized in that The free radical photoinitiator has a structure shown in Formula I: wherein R1 and R2 are each independently selected from a hydrocarbon group having 5 to 10 carbon atoms or a hydrocarbon group having 4 to 16 carbon atoms substituted by a hydrocarbonoxy group, a hydroxyl hydrocarbonoxy group, an ether hydrocarbonoxy group, an alkylenedioxy group, a hydrocarbonamino group, a dialkylamino group, a nitro group or a halogen group, or a coumarin group; Preferably, R1 and R2 are each independently selected from coumarinyl, coumarin vinyl, dimethylamino, diethylamino, phenyl, styryl, p-tolyl, p-tolyl vinyl, 3-ethylphenyl, 2-chlorophenyl, 3,4-dimethoxyphenyl, 3,4-dimethoxystyryl, 4-ethoxyphenyl, 3-isobutoxyphenyl, 3,4-methylenedioxyphenyl, 2,3-ethylenedioxyphenyl, 4-(2-hydroxyethoxy)-phenyl, 2-(2-hydroxyethoxy)-phenyl, 4-(4-(6-(amino)-1-propoxy)-phenyl, 4-bromophenyl, 4-nitrophenyl, 3-fluorophenyl, 4-methoxynaphthyl, 4-diethylaminophenyl, 2-dimethylaminophenyl, 3-isopropylaminophenyl, 4-dibutylamino-2-chlorophenyl, furanyl, furanvinyl, N-methylpyrrole, N-methylpyrrolevinyl, 7-(dimethylamino)coumarin, 7-(dimethylamino)coumarinvinyl, 7-(diethylamino)-coumarinyl, 7-(diethylamino)coumarinvinyl; More preferably, R1 and R2 are each independently selected from coumarin, coumarin vinyl, 7-(dimethylamino)coumarin, 7-(dimethylamino)coumarin vinyl, 7-(diethylamino)coumarin, 7-(diethylamino)coumarin vinyl, furanyl, furan vinyl, N-methylpyrrole, N-methylpyrrole vinyl, 3,4-dimethoxyphenyl, 3,4-dimethoxystyryl, phenyl, styryl, p-tolyl, p-tolyl vinyl.

6. The photoresist composition according to claim 1, characterized in that The auxiliary initiator is one or more of diphenyliodonium hexafluorophosphate, triethanolamine, N-methyldiethanolamine, ethyl 4-dimethylaminobenzoate, N-phenylglycine, and N,N-dimethyl-p-toluidine.

7. The photoresist composition according to claim 1, characterized in that The organic solvent includes one or more of toluene, o-xylene, m-xylene, p-xylene, m-trimethylbenzene, propylene glycol methyl ether acetate, propylene glycol methyl ether, chloroform, acetone, cyclopentanone, cyclohexanone, 4-methyl-2-pentanone, 2-heptanone, methanol, ethanol, n-propanol, isopropanol, butyl acetate and ethyl lactate.

8. The method for patterning a photoresist composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: The photoresist composition is coated on a substrate and dried to form a photoresist film, and the photoresist film is exposed to light and then placed in a developer to form a photoresist pattern.

9. The method for patterning a photoresist composition according to claim 8, characterized in that: The photolithography exposure method is visible light lithography, electron beam lithography or extreme ultraviolet lithography.

10. The method for patterning a photoresist composition according to claim 9, characterized in that: The light source of the visible light lithography method is visible light with a wavelength of 365 to 600 nm and a dosage of 10 to 500 mJ·cm -2 The electron beam lithography method is to expose the electron beam using an electron beam exposure machine, with a dose of 50 to 50000 pC cm -1 The light source of the EUV lithography method is EUV light with a wavelength of 13.5 nm and a dose of 5 to 500 mJ·cm -2 .

Citation Information

Cited By

  • Nanometer luminescent material and application thereof in photoresist

    CN121518133A